EFEKTIITAS PRENATAL YOGA TERHADAP KETIDAKNYAMANAN IBU HAMIL TRIMESTER III DI YAYASAN BUMI SEHAT, UBUD-BALI, INDONESIA - Ni Wayan Noviani; Ni Wayan Sukma Adnyani (JOMIS (Journal of Midwifery Science), 2021)
This study aims to determine the effectiveness of prenatal yoga in reducing the discomfort of third-semester pregnant women. Method: This type of research is the analytic and cross-sectional design. The number of samples is 50 pregnant women who meet the inclusion criteria by using a purposive sampling technique. The instrument data collection using a questionnaire that has been tested for validity and reliability. Bivariate analysis using chi-square correlation test and multivariate analysis using multiple logistic regression. Result: The result of the data shows that prenatal yoga is effective in reducing the discomfort of third-trimester pregnant women routinely by > 6 times. Chi-square test results show a significant effect of p-value <0.05. The multivariate result shows the most effective factor in reducing discomfort pregnant women was cramping with OR by 118.58 (95% CI: 6.01-2340.20), so it can be interpreted that prenatal yoga> 6 times effective in reducing cramps in pregnant women. Conclusion: From the result of research conducted, prenatal yoga is effective in reducing discomfort in third-semester pregnant women if done routinely or> 6 times.